2020
DOI: 10.4236/ojml.2020.105029
|View full text |Cite
|
Sign up to set email alerts
|

A Review Paper on the Syntactic Abilities of Individuals with Down Syndrome

Abstract: This systematic review aims to synthesize current findings on the syntactic abilities of individuals with Down Syndrome from childhood into adolescence and adulthood and discuss them in terms of the delayed or deviant pattern of development as well as in terms of the critical period for syntactic development. This literature search was conducted using research articles written only in the English language, but concerning syntax in any language, after a thorough search in the web databases, following the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Previous research has shown various impairments in language comprehension in individuals with Down syndrome [cf. review by Andreou and Chartomatsidou, 2020]. We would therefore like to stress the importance of addressing not only expressive but also receptive 10.3389/fpsyg.2023.1118659 Frontiers in Psychology 14 frontiersin.org abilities in language therapy, especially since limitations in language comprehension can easily be overlooked or remain unrecognized without suitable diagnostic instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown various impairments in language comprehension in individuals with Down syndrome [cf. review by Andreou and Chartomatsidou, 2020]. We would therefore like to stress the importance of addressing not only expressive but also receptive 10.3389/fpsyg.2023.1118659 Frontiers in Psychology 14 frontiersin.org abilities in language therapy, especially since limitations in language comprehension can easily be overlooked or remain unrecognized without suitable diagnostic instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Receptive grammatical abilities are often considered to be less affected than expressive skills ( Chapman et al, 1998 ), but many individuals with Down syndrome still exhibit difficulties in sentence comprehension (see review by Andreou and Chartomatsidou, 2020 ). Such difficulties often limit the comprehension of so-called non-canonical sentences in which the word order does not correspond to the unmarked constituent structure in a given language (e.g., passives or object-initial questions; Wimmer and Penke, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…On average, they reach the milestone of sentence production at approximately 3.5 to 5 years of age [96,97], but 30% of children with Down syndrome still do not speak in complete sentences by the age of 6 [29]. For children who do speak in sentences, limitations in syntax and complex sentence structure are still reported [29,98], and they also have a low mean length of utterance [99]. In general, children with Down syndrome have limited expressive vocabulary [30] and show initial weaknesses in function words such as prepositions, conjunctions, and pronouns [100], as well as on unfamiliar words [24,26,101].…”
Section: An Association Between Difficulties With Speech Fluency and The Level Of Language Skillsmentioning
confidence: 99%
“…Performance on receptive vocabulary tests keeps pace with or even exceeds nonverbal cognitive measures for individuals with Williams syndrome (Mervis & John, 2008), those with Down syndrome (Miolo, Chapman, & Sindberg, 2005), and those of undifferentiated etiology (Facon, Bollengier, & Grubar, 1993), particularly in late childhood, adolescence, or adulthood (Facon, Facon-Bollengier, & Grubar, 2002;Hoffmann et al, 2019). By contrast, syntactic development, both in comprehension and especially in expression, is often weaker than expected in view of the children's intellectual abilities (e.g., Abbeduto et al, 2016;Andreou & Chartomatsidou, 2020;Hilvert & Sterling, 2019).…”
Section: Introductionmentioning
confidence: 99%